Exploring Holocene palaeogeography in the 'white ribbon': a Mesolithic case study from the Northumberland coast. (7th December 2016) - Bicket, A. R.; Mellett, C. L.; Tizzard, L.; Waddington, C.
ABSTRACT: Mesolithic settlement sites preserved on the north‐east coast of England and in south‐east Scotland drive questions about the relationship between early human settlement and the Holocene palaeogeography of 'Doggerland'. Palaeogeographical reconstructions before 8000 years ago have been restricted by a lack of sea‐level index points and particularly by sparse nearshore geophysical and geological datasets required for such reconstructions. This paper presents new high‐resolution geophysical survey data from Northumberland's nearshore 'white ribbon' which provide a foundation for more accurate palaeogeographical reconstructions within which early prehistoric settlement sites can be more readily understood. High‐resolution bathymetry data collected in the nearshore adjacent to the Mesolithic house site at Howick are integrated with coastal LiDAR, seismic, geological and archaeological datasets to underpin palaeogeographical reconstructions. The reconstructions illustrate changing coastal landscapes during Early Holocene sea‐level rise. The data and interpretations provide a 'source‐to‐sea' context for understanding the archaeology at important sites such as Howick and Low Hauxley. Furthermore, they provide a basis for enhancing management of at‐risk coastal prehistoric archaeology and a framework to prospect for and protect further vulnerable nearshore archaeological heritage.